PERIPORTAL CARDIOMYOPATHIES (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
Periportal cardiomyopathies are rare and complex cardiovascular diseases associated with the development of fibrosis in the periportal region of the liver, which subsequently affects myocardial structure and function. These conditions, although uncommon, significantly contribute to morbidity and mortality in affected patients. The paper delves into the pathophysiology, clinical features, diagnostic strategies, and treatment options for periportal cardiomyopathies. Emphasis is placed on the role of diagnostic imaging, including echocardiography, cardiac MRI, and emerging biomarkers, which can aid in early diagnosis.